Interfacial Dynamics and Its Relations with ?Negative? Surface Viscosities Measured at Water?Air Interfaces Covered with a Cationic Surfactant - Cuenca, Victor E (Langmuir : the ACS journal of surfaces and colloids, 2019)
We studied the dynamics of a cationic surfactant monolayer, Gemini 12-2-12, at the air?water interface for surfactant aqueous solutions at concentrations below the critical micelle concentration. We present surface rheology experiments performed in a Langmuir trough by the oscillatory barrier technique. From these, we found negative surface viscosities at certain frequencies. We demonstrate that this unphysical result is a consequence of an unconsidered surfactant dynamics within the interfacial region. By surface pressure relaxation experiments, after a sudden modification of the interfacial area and by dynamic surface tension and surface potential measurements, several relaxation phenomena and relaxation times were identified. We found that surfactant adsorption and desorption processes are asymmetric: the characteristic times and the number of processes involved in the mechanisms of adsorption and desorption are different. This asymmetry invalidates the usual data analysis procedure that leads to the negative viscosities. Similar mechanisms could be at the origin of the negative viscosities reported in other systems, a possibility that remains to be explored